2011
DOI: 10.4103/0975-9476.85551
|View full text |Cite
|
Sign up to set email alerts
|

Antistress activity of Argyreia speciosa roots in experimental animals

Abstract: The antistress effect of a seven-day treatment (100 and 200 mg / kg, p.o.) of the hydroalcoholic extract of Argyreia speciosa root (ASE) was evaluated by using the swimming endurance test, acetic acid–induced writhing test, pentylenetetrazole-induced convulsion test, anoxic tolerance test, cold-restraint, stress-induced gastric ulcers, aspirin-induced ulcers, and biochemical, and histopathological changes in the cold-restraint stress test. The immunomodulatory activity was also evaluated for the same doses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It plays an important role in central integration of hypothalamic-pituitary-adrenocortical (HPA) stress reaction. None adequate level of GABA in plasma has been related to the development of acute posttraumatic stress disorder [ 21 , 22 ]. On the other hand, previous study has reported that ethanol extract of Rubia cordifolia can stimulate the brain GABA level that subsequently reduced the dopamine and plasma corticosterone levels [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in central integration of hypothalamic-pituitary-adrenocortical (HPA) stress reaction. None adequate level of GABA in plasma has been related to the development of acute posttraumatic stress disorder [ 21 , 22 ]. On the other hand, previous study has reported that ethanol extract of Rubia cordifolia can stimulate the brain GABA level that subsequently reduced the dopamine and plasma corticosterone levels [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have also been reported that the plants having anti-stress property will reduce the number of writhes. [ 2 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported the same result. [ 2 24 26 ] Stress-induced rise in blood glucose, total cholesterol and triglyceride levels were significantly reduced by both extracts of R. diffusa at a dose of 300 mg/kg b.w. indicating their anti-stress potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pace of modern life, the constant effect on the body of adverse exogenous and endogenous factors (noise, vibration, bacterial toxins, viruses, radiation, microwaves), as well as intense social the situation can be stressprovocative factors (Patel et al, 2011;Oladipo and Ibukun, 2016.). Stress beyond physiological adaptation is sharply negative and adversely affects activities of organs and systems, primarily those in which there is a high metabolic activitythe brain and myocardium, as well as the thymolymphatic apparatus (Oladipo and Ibukun, 2016).…”
Section: Evaluation Of the Studied Extracts Effect On The Change In The Mitochondrial Function Of The Rat Brain And Myocardium Under Acutmentioning
confidence: 99%